The fallen - Baldacci, David (Baldacci, David. Amos Decker series., 2018)
Amos Decker and his FBI colleague Alex Jamison are in Baronville, Pennsylvania, visiting Alex's sister and her family. It's a bleak place: a former mill and mining town with a crumbling economy and rampant opioid addiction. Decker has only been there a few hours when he stumbles on a horrific double murder scene. Then the next killing hits sickeningly close to home. With the lives of people he cares about suddenly hanging in the balance, Decker realizes that the recent string of deaths is only one small piece of a much larger scheme -- with consequences that will reach far beyond Baronville. But when one mistake could cost him everything, Decker finds that his previously infallible memory may not be so trustworthy after all.